Effect of zinc oxide nanoparticle supplementation on the enhanced production of surfactin and iturin lipopeptides of endophytic Bacillus sp. Fcl1 and its ameliorated antifungal activity. Issue 2 (31st October 2020) - Ravi, Aswani; Nandayipurath, Vipina Vinod Thazhe; Rajan, Sukanya; Salim, Simi Asma; Khalid, Nejumal Kannankeril; Aravindakumar, Charuvila T; Krishnankutty, Radhakrishnan Edayileveettil
Abstract: BACKGROUND: Lipopeptides from the Bacillus spp. possess an excellent spectrum of antimicrobial properties which make them suitable candidates to be explored for the food, agricultural, pharmaceutical and biotechnological applications. As the low yield of the lipopeptides limits their applications, methods to enhance their production are highly significant. RESULTS: In this study, extracts prepared from endophytic Bacillus sp. Fcl1 cultured in the presence of various supplements were screened for antifungal activity against Pythium aphanidermatum. From the results, the supplementation of carbon sources and zinc oxide nanoparticles (ZnONPs) was found to have an enhancement effect on the antifungal activity of Bacillus sp. Fcl1. Among these, the highest antifungal activity (73.2%) could be observed for the Fcl1 sample cultured with 5 mg L −1 of ZnONP supplementation. The growth of Fcl1 in the presence of ZnONPs also indicated its compatibility with the nano‐supplement in the concentration range used. By liquid chromatography quadrupole time‐of‐flight mass spectrometry (LC‐Q‐TOF‐MS) analysis, the synthesis of increased numbers of lipopeptide surfactin derivatives could be identified from the extracts of Fcl1 prepared from the carbon sources and ZnONP‐supplemented cultures. In addition to the surfactin derivatives, the presence of another lipopeptide iturin was also detected from the extracts of Fcl1 cultured with ZnONPs. CONCLUSION: ZnONP supplementation was found to enhance antifungal activity and lipopeptide production in the Bacillus sp. Fcl1. The use of nanoparticles to enhance the antifungal mechanisms of Fcl1 as observed in the study provides novel insights to explore its applications for sustainable agricultural productivity. Abstract : The enhanced antifungal activity and modulation of the lipopeptide profile of Bacillus sp. Fcl1 due to culture supplementation with ZnONPs suggests the potential of nanoelicitors for the functional improvement of agriculturally important microorganisms. © 2020 Society of Chemical Industry